Graphite composite material, preparation method thereof and lithium ion battery
Through a preparation method of graphite composite material, amide graphite is crosslinked with substances such as lithium peroxide and mixed with curing agent and asphalt for treatment, the problem of low efficiency of artificial graphite materials is solved for the first time, and efficient and stable lithium-ion battery performance is achieved.
Patent Information
- Application Number
- CN202510036365.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The first-time efficiency of artificial graphite materials in the prior art is low, limiting the increase in energy density of lithium-ion batteries.
Through a method of preparing a graphite composite material, it includes obtaining amide graphite and cross-linking with lithium peroxide, hydrogen peroxide solution, and organic acid reagent to form an intermediate. Then, the intermediate is mixed with a curing agent containing an aldehyde group and asphalt, and curing and carbonizing reactions are carried out to form a graphite composite material with a high degree of crosslinking and stable structure.
It improves the first-time efficiency, fast charging performance and high-temperature performance of graphite materials, reduces the change in graphite volume during charging and discharging, and reduces the interface impedance and polarization.
Smart Images

Figure CN119898767A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery material preparation, and in particular to a graphite composite material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] At present, the negative electrode material of commercial lithium batteries is mainly artificial graphite, and its initial efficiency is relatively low. For example, when lithium iron phosphate is used as the positive electrode material, the initial efficiency of the positive electrode is about 96%, and the initial efficiency of artificial graphite is between 92 and 94%. Therefore, when these two positive and negative electrodes are used to make lithium-ion batteries, the negative electrode becomes the key factor limiting the improvement of the energy density of lithium iron phosphate batteries. Summary of the invention
[0003] The main purpose of the present invention is to provide a graphite composite material and a preparation method thereof and a lithium ion battery, aiming to solve the problem of low initial efficiency of artificial graphite materials in the prior art.
[0004] To achieve the above object, the present invention provides a method for preparing a graphite composite material, comprising the following steps:
[0005] S10, obtaining amidated graphite, mixing the amidated graphite, lithium peroxide, a hydrogen peroxide solution, and an organic acid reagent, and performing a cross-linking reaction to obtain an intermediate;
[0006] S20, mixing the intermediate with a curing agent containing an aldehyde group and asphalt, and sequentially performing a curing reaction and a carbonization reaction to obtain the graphite composite material.
[0007] In one embodiment, in step S10, the step of obtaining amidated graphite includes:
[0008] S01, obtaining carboxylated graphite, mixing the carboxylated graphite, an organic solvent, and an acyl chloride reagent, and performing an acyl chloride reaction to obtain acyl chloride graphite;
[0009] S02, mixing the acyl chloride graphite with a solution of an amino compound, and performing an amide reaction to obtain amidated graphite.
[0010] In one embodiment, in step S01, the step of obtaining carboxylated graphite includes:
[0011] Graphite is mixed with a mixed acid solution and subjected to an oxidation reaction to obtain carboxylated graphite.
[0012] In one embodiment, the mass ratio of graphite to mixed acid is 100:(500-1000); and / or,
[0013] The mixed acid comprises sulfuric acid and nitric acid, wherein the volume ratio of sulfuric acid to nitric acid is (1-3):1, the mass percentage concentration of sulfuric acid is 70wt%-98wt%, and the mass percentage concentration of nitric acid is 50wt%-70wt%; and / or,
[0014] The oxidation reaction time is 12 to 72 hours.
[0015] In one embodiment, in step S01, the mass ratio of the carboxylated graphite, the organic solvent and the acyl chloride reagent is 100:(500-1000):(10-50); and / or,
[0016] In step S01, the organic solvent includes N-N-dimethylformamide; and / or,
[0017] In step S01, the acyl chloride reagent includes thionyl chloride; and / or,
[0018] In step S01, the temperature of the acyl chlorination reaction is 50-100° C.; and / or,
[0019] In step S01, the acyl chlorination reaction time is 12 to 24 hours; and / or,
[0020] In step S02, the mass ratio of the graphite chloride to the solution of the amino compound is 100:(10-30); and / or,
[0021] In step S02, the mass percentage concentration of the amino compound in the amino compound solution is 3wt% to 30wt%; and / or,
[0022] In step S02, the amino compound in the amino compound solution includes at least one of aniline, dimethylamine and trimethylamine; and / or,
[0023] In step S02, the amide reaction time is 1 to 6 hours; and / or,
[0024] The temperature of the amide reaction is 0-10°C.
[0025] In one embodiment, in step S10:
[0026] The mass ratio of the amidated graphite, the lithium peroxide, the hydrogen peroxide solution and the organic acid reagent is 100:(10-30):(10-30):(5-15), and the mass percentage concentration of hydrogen peroxide in the hydrogen peroxide solution is 10wt%-30wt%; and / or,
[0027] The organic acid reagent comprises one of acetic acid, malic acid, oxalic acid or citric acid; and / or,
[0028] The temperature of the cross-linking reaction is 50-100° C.; and / or,
[0029] The cross-linking reaction time is 1 to 6 hours.
[0030] In one embodiment, in step S20:
[0031] The mass ratio of the intermediate, the aldehyde-containing curing agent and the asphalt is 100:(5-15):(5-15); and / or,
[0032] The aldehyde-containing curing agent comprises at least one of p-hydroxybenzaldehyde, vanillin and syringaldehyde; and / or,
[0033] The curing reaction temperature is 400-600° C.; and / or,
[0034] The curing reaction time is 1 to 6 hours; and / or,
[0035] The temperature of the carbonization reaction is 1000-1400° C.; and / or,
[0036] The carbonization reaction time is 1 to 6 hours.
[0037] The present invention also provides a graphite composite material, which is prepared by the above-mentioned method for preparing the graphite composite material.
[0038] In one embodiment, the graphite composite material has a particle size of 10 to 15 μm.
[0039] The present invention also provides a lithium ion battery, comprising the graphite composite material prepared by the aforementioned method for preparing the graphite composite material or the aforementioned graphite composite material.
[0040] In the technical solution of the present invention, in step S10, the amidated graphite is a multilayer structure and has amide groups connected to its surface. The amidated graphite is mixed with lithium peroxide, hydrogen peroxide solution, and an organic acid reagent. Part of the lithium peroxide in the system is decomposed into lithium ions and hydrogen peroxide under an acidic environment at room temperature. The hydrogen peroxide is further decomposed into oxygen free radicals. The oxygen free radicals cross-link with part of the amide groups (-CONHOH) on the surface of the amidated graphite to form peroxyamide groups, which further undergo cross-linking reactions with nearby adjacent amide groups or peroxyamide groups to form a first three-dimensional network structure. In the cross-linking process, the generated lithium ions enter the interlayer spacing of the graphite, thereby expanding the interlayer spacing of the graphite. At the same time, other lithium-containing compounds generated by lithium peroxide exist in the three-dimensional network structure to obtain an intermediate, which is doped with nitrogen elements provided by the amide groups and lithium elements provided by the lithium peroxide. In step S20, the intermediate is mixed with an aldehyde-containing curing agent and asphalt and ball-milled to make them uniformly dispersed, and then cured. During the process, the aldehyde group (-CHO) in the organic curing agent containing aldehyde group undergoes condensation reaction with the uncrosslinked amide group (-CONH2) to generate a structure connected by methylene bridge (-CH2-), and multiple methylene bridges are connected to form a more complex three-dimensional cross-linked network, that is, the second three-dimensional network structure, which improves the structural stability of the graphite material; then a carbonization treatment is performed to carbonize the organic matter in the asphalt and deposit it on the surface of the intermediate to form a dense soft carbon layer. Such a preparation process improves the cross-linking degree of the graphite surface, the interlayer spacing of the graphite and the stability of the graphite structure, thereby increasing the speed of lithium removal and lithium insertion of the graphite material, and the incorporation of lithium also compensates for the defects of the graphite itself, reducing the change in the volume of the graphite during the charge and discharge process, and the greater the degree of cross-linking, the greater the specific surface area of the composite material, so that the graphite has the advantages of fewer defects and larger specific surface area; soft carbon coating and lithium nitrogen doping jointly reduce the interfacial impedance of the graphite material, reduce the polarizability of the graphite material, and improve the initial efficiency, fast charging performance and high temperature performance of the graphite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0042] Figure 1 This is a scanning electron microscope image (SEM) of the graphite composite material in Example 1 provided by the present invention.
[0043] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0044] To make the purpose, technical scheme and advantages of the embodiment of the present invention clearer, the technical scheme in the embodiment of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiment, it is carried out according to the normal conditions or the conditions recommended by the manufacturer. If the reagents or instruments used do not specify the manufacturer, they are all conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes, taking "A and / or B" as an example, including scheme A, or scheme B, or schemes that A and B meet at the same time. In addition, the technical schemes between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in the field to achieve. When the combination of technical solutions is contradictory or cannot be achieved, it should be considered that the combination of such technical solutions does not exist, and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention.
[0045] At present, the negative electrode material of commercial lithium batteries is mainly artificial graphite, and its initial efficiency is relatively low. For example, when lithium iron phosphate is used as the positive electrode material, the initial efficiency of the positive electrode is about 96%, and the initial efficiency of artificial graphite is between 92 and 94%. Therefore, when these two positive and negative electrodes are used to make lithium-ion batteries, the negative electrode becomes the key factor limiting the improvement of the energy density of lithium iron phosphate batteries.
[0046] The main reasons for the low initial efficiency of artificial graphite are: (1) Artificial graphite materials have a large specific surface area and many defects, which cause the loss of lithium ions during the initial charge and discharge process, thereby reducing the initial efficiency; (2) Artificial graphite materials have large polarization, and lithium insertion and removal are difficult, so the initial efficiency is low.
[0047] At present, the main measures to improve the initial efficiency of graphite are: (1) shaping the graphite material to reduce defects and specific surface area, but this method will reduce the dynamic properties of the material; (2) reducing the coating amount of the graphite material, but this method will cause the dynamic properties of the material to decrease and the high temperature performance to deteriorate.
[0048] In view of this, the present invention provides a method for preparing a graphite composite material, comprising the following steps:
[0049] S10, obtaining amidated graphite, mixing the amidated graphite, lithium peroxide, a hydrogen peroxide solution, and an organic acid reagent, and performing a cross-linking reaction to obtain an intermediate;
[0050] S20, mixing the intermediate with a curing agent containing an aldehyde group and asphalt, and sequentially performing a curing reaction and a carbonization reaction to obtain the graphite composite material.
[0051] In the technical solution of the present invention, in step S10, the amidated graphite is a multilayer structure and has amide groups connected to its surface. The amidated graphite is mixed with lithium peroxide, hydrogen peroxide solution, and an organic acid reagent. Part of the lithium peroxide in the system is decomposed into lithium ions and hydrogen peroxide under an acidic environment at room temperature. The hydrogen peroxide is further decomposed into oxygen free radicals. The oxygen free radicals cross-link with part of the amide groups (-CONHOH) on the surface of the amidated graphite to form peroxyamide groups, which further undergo cross-linking reactions with neighboring amide groups or peroxyamide groups to form a three-dimensional network structure. In the cross-linking process, the generated lithium ions enter the interlayer spacing of the graphite, thereby expanding the interlayer spacing of the graphite. At the same time, other lithium-containing compounds generated by lithium peroxide exist in the three-dimensional network structure to obtain an intermediate, which is doped with nitrogen elements provided by the amide groups and lithium elements provided by the lithium peroxide. In step S20, the intermediate is mixed with an aldehyde-containing curing agent and asphalt and ball-milled to make them uniformly dispersed, and then cured. During the curing process, the aldehyde group (-CHO) in the organic curing agent containing aldehyde group undergoes a condensation reaction with the uncrosslinked amide group (-CONH2) to generate a structure connected by a methylene bridge (-CH2-). Multiple methylene bridges are connected to form a more complex three-dimensional cross-linked network, thereby improving the structural stability of the graphite material. Subsequently, a carbonization treatment is performed to carbonize the organic matter in the asphalt and deposit it on the surface of the intermediate to form a dense soft carbon layer. Such a preparation process improves the cross-linking degree of the graphite surface, the interlayer spacing of the graphite and the stability of the graphite structure, thereby increasing the speed of lithium removal and lithium insertion of the graphite material. The incorporation of lithium also compensates for the defects of the graphite itself and reduces the change in the volume of the graphite during the charge and discharge process. The greater the degree of cross-linking, the greater the specific surface area of the composite material, so that the graphite has the advantages of fewer defects and larger specific surface area. The soft carbon coating and lithium nitrogen doping jointly reduce the interfacial impedance of the graphite material, reduce the polarizability of the graphite material, and improve the initial efficiency, fast charging performance and high temperature performance of the graphite material.
[0052] That is, two oxidants, lithium peroxide and hydrogen peroxide solution, oxidize the amidated graphite under acidic conditions. On the one hand, the oxygen free radicals generated by hydrogen peroxide attack the amide groups on the surface of graphite, causing it to be oxidized and cross-linked to form a three-dimensional network structure. On the other hand, lithium peroxide dissociates lithium ions and is doped into the interlayer gaps of graphite to obtain an intermediate. The intermediate is cross-linked with a curing agent to form a more complex three-dimensional network structure. The carbonization treatment coats the graphite surface with soft carbon, thereby improving the stability, initial efficiency, fast charging performance and high temperature performance of the graphite material.
[0053] In some embodiments of the present invention, in step S10, the step of obtaining amidated graphite includes: S01, obtaining carboxylated graphite, mixing the carboxylated graphite, an organic solvent, and an acyl chloride reagent, performing an acyl chloride reaction, and obtaining acyl chloride graphite; S02, mixing the acyl chloride graphite with a solution of an amino compound, performing an amide reaction, and obtaining amidated graphite.
[0054] In the technical scheme of the present invention, the surface of carboxylated graphite has more carboxylic acid groups. Carboxylated graphite is mixed with an organic solvent and an acyl chloride reagent, so that the carboxylic acid groups on the surface of graphite react with the acyl chloride reagent, so that the carboxylic acid groups are converted into acyl chloride groups to obtain acyl chloride graphite; after the acyl chloride graphite is mixed with a solution of an amino compound, the amino group of the amino compound reacts with the acyl chloride group of graphite, so that the acyl chloride group is converted into an amide group to obtain amide graphite. The surface of the amide graphite obtained by the above method is more evenly doped with nitrogen, so that a stable covalent bond is formed between nitrogen and carbon, thereby improving the thermal stability and electrical conductivity of the graphite material.
[0055] In some embodiments of the present invention, in step S01, the step of obtaining carboxylated graphite includes: mixing graphite with a mixed acid solution, performing an oxidation reaction, and obtaining carboxylated graphite. The mixed acid is used to oxidize the graphite, so that oxygen-containing functional groups mainly composed of carboxylic acid groups are introduced into the graphite surface, and the oxygen-containing functional groups significantly improve the hydrophilicity of the graphite, so that the graphite has good dispersibility in water and other polar solvents. In addition, during the oxidation process, the π-π stacking effect between graphite layers is weakened, resulting in an increase in the interlayer spacing, which is conducive to the embedding of lithium ions.
[0056] In some embodiments of the present invention, the mass ratio of the graphite to the mixed acid is 100:(500-1000). The mass ratio within the above range can make the graphite more fully oxidized, so that more carboxyl groups are formed on its surface.
[0057] In some embodiments of the present invention, the mixed acid includes sulfuric acid and nitric acid, wherein the volume ratio of sulfuric acid to nitric acid is (1-3):1, the mass percentage concentration of sulfuric acid is 70wt%-98wt%, and the mass percentage concentration of nitric acid is 50wt%-70wt%. The oxidation rate of graphite using nitric acid and sulfuric acid of the above mass percentage concentrations is faster, and more carboxyl groups can be formed on the graphite surface faster.
[0058] In some embodiments of the present invention, the oxidation reaction time is 12 to 72 hours. The oxidation reaction time can be 12 hours, 36 hours or 72 hours. The oxidation reaction time within the above range can ensure that more carboxyl groups are formed on the graphite surface.
[0059] In some embodiments of the present invention, in step S01, the mass ratio of the carboxylated graphite, the organic solvent and the acyl chloride reagent is 100:(500-1000):(10-50). The mass ratio within the above range can ensure that the carboxyl groups on the graphite surface can be fully converted into acyl chloride groups.
[0060] In some embodiments of the present invention, in step S01, the organic solvent includes N-N-dimethylformamide. The organic solvent can make the carboxylated graphite have better dispersibility and solubility, prevent graphite from agglomerating, and thus enable it to react more fully with the acyl chloride reagent.
[0061] In some embodiments of the present invention, in step S01, the acyl chloride reagent includes thionyl chloride. The acyl chloride reagent can convert the carboxyl groups on the graphite surface into acyl chloride groups more quickly.
[0062] In some embodiments of the present invention, in step S01, the temperature of the chlorination reaction is 50-100°C; and / or, the chlorination reaction time is 12-24 hours. The chlorination reaction time and temperature within the above range can ensure that the carboxyl groups on the surface of the carboxylated graphite undergo chlorination reaction more fully and are converted into acyl chloride groups, thereby obtaining graphite with a higher degree of chlorination.
[0063] In some embodiments of the present invention, in step S02, the mass ratio of the acyl chloride graphite to the amino compound solution is 100:(10-30). The mass ratio within the above range can ensure that the acyl chloride groups in the acyl chloride graphite are fully converted into amide groups.
[0064] In some embodiments of the present invention, in step S02, the mass percentage concentration of the amino compound in the amino compound solution is 3wt% to 30wt%. The mass percentage concentration within the above range can ensure that more amino groups are provided to react with the acyl chloride groups of the acyl chloride graphite for amide reaction.
[0065] In some embodiments of the present invention, in step S02, the amino compound in the solution of the amino compound includes at least one of aniline, dimethylamine and trimethylamine. The above amino compound can react well with the acyl chloride group of the acyl chloride graphite to obtain amidated graphite more quickly.
[0066] In some embodiments of the present invention, in step S02, the amide reaction time is 1 to 6 hours; and / or, the amide reaction temperature is 0 to 10° C. The amide reaction time and temperature within the above range can ensure that the amide reaction is more complete, so that the acyl chloride groups in the acyl chloride graphite are more fully converted into amide groups.
[0067] In some embodiments of the present invention, in step S10: In some embodiments of the present invention, the mass ratio of the amidated graphite, the lithium peroxide, the hydrogen peroxide solution and the organic acid reagent is 100: (10-30): (10-30): (5-15), and the mass percentage concentration of hydrogen peroxide in the hydrogen peroxide solution is 10wt%-30wt%. The mass ratio within the above range can ensure that lithium peroxide can hydrolyze more lithium ions in an acidic environment, and hydrogen peroxide can decompose to obtain more oxygen free radicals, thereby attacking the amide groups on the surface of the amidated graphite to form a cross-linked structure. The mass percentage concentration of hydrogen peroxide in the hydrogen peroxide solution within the above range can ensure that more oxygen free radicals are generated, thereby increasing the rate of the cross-linking reaction.
[0068] In some embodiments of the present invention, in step S10: the organic acid reagent includes one of acetic acid, malic acid, oxalic acid or citric acid. The organic acid reagent can dissociate lithium peroxide into lithium ions more quickly.
[0069] In some embodiments of the present invention, in step S10: the temperature of the cross-linking reaction is 50-100° C.; and / or the time of the cross-linking reaction is 1-6 hours. The temperature and time of the cross-linking reaction within the above range can make the oxygen free radicals and the amide groups on the surface of the amidated graphite cross-linked more fully, and the cross-linked products further cross-link with the adjacent groups to form a three-dimensional network structure with a good degree of cross-linking.
[0070] In some embodiments of the present invention, in step S20: the mass ratio of the intermediate, the curing agent containing aldehyde groups and the asphalt is 100:(5-15):(5-15). The mass ratio within the above range can ensure that the curing agent can provide more aldehyde groups to cross-link with the intermediate to form more cross-linked networks, and at the same time can ensure that the asphalt can fully form a soft carbon layer covering the graphite surface during the carbonization process.
[0071] In some embodiments of the present invention, in step S20: the aldehyde-containing curing agent includes at least one of p-hydroxybenzaldehyde, vanillin and syringaldehyde. The above curing agent can react well with the amide group in the intermediate to form a cross-linked structure.
[0072] In some embodiments of the present invention, in step S20: the temperature of the curing reaction is 400-600°C; and / or, the time of the curing reaction is 1-6 hours. The curing time and temperature within the above range can ensure that the aldehyde group of the curing agent reacts and crosslinks with the group of the intermediate more fully, introduce more methylene groups into the first three-dimensional network structure, so as to form a three-dimensional network structure with a stronger degree of crosslinking, and improve the specific surface area and stability of the graphite material.
[0073] In some embodiments of the present invention, in step S20: the temperature of the carbonization reaction is 1000-1400°C; and / or, the time of the carbonization reaction is 1-6 hours. The time and temperature of the carbonization reaction within the above range can ensure that the hydrogen elements in the asphalt and even the second three-dimensional network structure are volatilized, leaving a denser soft carbon layer in the network structure and graphite with a larger specific surface area.
[0074] The present invention also provides a graphite composite material, which is prepared by the above-mentioned graphite composite material preparation method. The graphite composite material has all the beneficial effects of the above-mentioned graphite composite material preparation method, which will not be described one by one here.
[0075] In some embodiments of the present invention, the particle size of the graphite composite material is 10-15 μm. The particle size of the graphite composite material can be 10 μm, 12 μm or 5 μm. The particle size within this range can ensure that the subsequent processing is less difficult.
[0076] The present invention also provides a lithium ion battery, comprising the graphite composite material prepared by the aforementioned method for preparing the graphite composite material or the aforementioned graphite composite material. Therefore, the lithium ion battery has all the beneficial effects of the aforementioned method for preparing the graphite composite material or the aforementioned graphite material, which will not be described one by one here.
[0077] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.
[0078] Example 1
[0079] A method for preparing a graphite composite material comprises the following steps:
[0080] S01-S02, adding 100g of artificial graphite to 500g of mixed acid solution (concentrated sulfuric acid: concentrated nitric acid = 1:1, the mass percentage concentration of sulfuric acid in concentrated sulfuric acid is 90wt%, and the mass percentage concentration of nitric acid in concentrated nitric acid is 60wt%), soaking for 48h, filtering, washing with deionized water, and vacuum drying at 80°C for 24h to obtain carboxylated graphite;
[0081] 100 g of carboxylated graphite was added to 800 g of thionyl chloride and mixed evenly, and then 30 g of N,N-dimethylformamide was added, reacted at 80° C. for 18 h, filtered, and the filter residue was washed with tetrahydrofuran and then dried at 80° C. in vacuum for 24 h to obtain chlorinated graphite;
[0082] 100 g of acyl chloride graphite was added to 20 g of aniline solution (the mass percentage concentration of aniline in the aniline solution was 3 wt%), followed by ultrasonic reaction at 4° C. for 3 h, filtering, and vacuum drying the filter residue at 80° C. for 24 h to obtain amidated graphite;
[0083] S10, adding 100 g of amidated graphite to 2000 g of anhydrous acetic acid and dispersing the mixture uniformly, then adding 20 g of 5 wt% lithium perhydride in N-methylpyrrolidone and 20 g of 30 wt% hydrogen peroxide, reacting at 80° C. for 3 h, filtering, and drying the residue in vacuum at 80° C. for 24 h to obtain an intermediate;
[0084] S20, adding 100g of the intermediate, 10g of p-hydroxybenzaldehyde and 10g of asphalt into a ball mill and mixing them evenly, and transferring them into a tubular furnace, first heating them to 500°C for curing for 3h, and then heating them to 1200°C for carbonization for 3h to obtain a graphite composite material.
[0085] Example 2
[0086] A method for preparing a graphite composite material comprises the following steps:
[0087] S01-S02, adding 100g of artificial graphite to 1000g of mixed acid solution (concentrated sulfuric acid: concentrated nitric acid = 3:1, the mass percentage concentration of sulfuric acid in concentrated sulfuric acid is 70wt%, and the mass percentage concentration of nitric acid in concentrated nitric acid is 50wt%), soaking for 12h, filtering, washing with deionized water, and vacuum drying at 80°C for 24h to obtain carboxylated graphite;
[0088] 100 g of carboxylated graphite was added to 500 g of thionyl chloride and mixed evenly, and then 10 g of N,N-dimethylformamide was added, reacted at 50° C. for 24 h, filtered, and the filter residue was washed with tetrahydrofuran and then dried at 80° C. in vacuum for 24 h to obtain chlorinated graphite;
[0089] 100 g of acyl chloride graphite was added to 10 g of dimethylamine solution (the mass percentage concentration of dimethylamine in the dimethylamine solution was 10 wt%), followed by ultrasonic reaction at 10° C. for 1 h, filtering, and vacuum drying the filter residue at 80° C. for 24 h to obtain amidated graphite;
[0090] S10, adding 100 g of amidated graphite to 2000 g of anhydrous acetic acid and dispersing the mixture uniformly, then adding 10 g of 10 wt% lithium perhydride in N-methylpyrrolidone and 10 g of 30 wt% hydrogen peroxide, reacting at 50° C. for 6 h, filtering, and drying the residue in vacuum at 80° C. for 24 h to obtain an intermediate;
[0091] S20, adding 100 g of the intermediate, 5 g of vanillin and 5 g of asphalt into a ball mill and mixing them evenly, and transferring them into a tubular furnace, first heating them to 400° C. for curing for 6 h, and then heating them to 1000° C. for carbonization for 6 h to obtain a graphite composite material.
[0092] Example 3
[0093] A method for preparing a graphite composite material comprises the following steps:
[0094] S01-S02, adding 100g of artificial graphite to 500g of mixed acid solution (concentrated sulfuric acid: concentrated nitric acid = 2:1, the mass percentage concentration of sulfuric acid in concentrated sulfuric acid is 95wt%, and the mass percentage concentration of nitric acid in concentrated nitric acid is 70wt%), soaking for 72h, filtering, washing with deionized water, and vacuum drying at 80°C for 24h to obtain carboxylated graphite;
[0095] 100 g of carboxylated graphite was added to 1000 g of thionyl chloride and mixed evenly, and then 50 g of N,N-dimethylformamide was added, and the mixture was reacted at 100° C. for 12 h, filtered, and the residue was washed with tetrahydrofuran and then dried at 80° C. in a vacuum oven for 24 h to obtain chlorinated graphite;
[0096] 100 g of acyl chloride graphite was added to 30 g of trimethylamine solution (the mass percentage concentration of trimethylamine in the trimethylamine solution was 30 wt%), followed by ultrasonic reaction at 0° C. for 6 h, filtering, and vacuum drying the filter residue at 80° C. for 24 h to obtain amidated graphite;
[0097] S10, adding 100 g of amidated graphite to 2000 g of anhydrous acetic acid and dispersing the mixture evenly, then adding 30 g of 1 wt% lithium perhydride in N-methylpyrrolidone organic solution and 30 g of 30 wt% hydrogen peroxide, reacting at 100° C. for 1 h, filtering, and drying the residue in vacuum at 80° C. for 24 h to obtain an intermediate;
[0098] S20, adding 100g of the intermediate, 15g of syringaldehyde and 15g of asphalt into a ball mill and mixing them evenly, and transferring them into a tubular furnace, first heating them to 600°C for curing for 1h, and then heating them to 1400°C for carbonization for 1h to obtain a graphite composite material.
[0099] Comparative Example 1
[0100] Compared with Example 1, Comparative Example 1 is the same as Example 1 except that the amidated graphite in step S10 is replaced by artificial graphite.
[0101] Comparative Example 2
[0102] Compared with Example 1, Comparative Example 2 is the same as Example 1 except that lithium peroxide is not added in step S10.
[0103] Comparative Example 3
[0104] Compared with Comparative Example 1, Comparative Example 3 is the same as Comparative Example 1 except that lithium peroxide is not added in step S10.
[0105] Comparative Example 4
[0106] Compared with Example 1, Comparative Example 4 is the same as Example 1 except that lithium peroxide and hydrogen peroxide are not added in step S10.
[0107] Comparative Example 5
[0108] Compared with Example 1, Comparative Example 5 is the same as Example 1 except that no curing agent is added in step S20.
[0109] Comparative Example 6
[0110] Compared with Comparative Example 4, Comparative Example 6 is the same as Comparative Example 4 except that no curing agent is added in step S20.
[0111] Performance Testing
[0112] The graphite composite material prepared in Example 1 was tested by scanning electron microscope (SEM), and the results are as follows: Figure 1 shown.
[0113] Depend on Figure 1 It can be seen that the material presents a secondary granular structure with a particle size between 10 and 15 μm.
[0114] The properties of the graphite composite materials in Examples 1 to 3 and Comparative Examples 1 to 6 were characterized in the following manner:
[0115] The tap density and specific surface area of graphite composite materials were tested according to the test method in standard GB / T-24533-2019 "Graphite Anode Materials for Lithium-ion Batteries";
[0116] The powder resistivity of graphite composite materials was tested by a four-probe tester;
[0117] The diffusion coefficient of graphite composites was tested by constant current intermittent titration technique (GITT);
[0118] The test results are shown in Table 1.
[0119] Table 1 Performance characteristics of negative electrode materials in Examples 1 to 3 and Comparative Examples 1 to 6
[0120]
[0121] It can be seen from Table 1 that the resistivity of the graphite composite materials prepared in Examples 1 to 3 is significantly better than that of the comparative example. The reason is that doping heteroatoms in the graphite composite materials improves the electronic conductivity of the material and the lithium ions thereof improve the lithium ion transmission rate of the material, thereby improving the diffusion coefficient of the material and reducing the resistivity.
[0122] The graphite composite materials prepared in Examples 1 to 3 and the graphite composite materials in Comparative Examples 1 to 6 were respectively assembled into button batteries according to the following method:
[0123] The graphite composite negative electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were used as negative electrodes and assembled into button cells with lithium sheets, electrolytes and separators in a glove box with argon and water content less than 0.1 ppm. The separator was celegard 2400; the electrolyte was a solution of LiPF6, in which the concentration of LiPF6 was 1 mol / L, and the solvent was a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DMC) mixed in a weight ratio of 1:1.
[0124] The performance of the 9 groups of button batteries prepared was tested using a blue battery tester, and the test conditions were:
[0125] First discharge capacity: Charge and discharge at a rate of 0.1C, with a voltage range of 0.005-2V. Stop after 3 cycles, and then test the discharge capacity at 1C.
[0126] Cycle performance: 25±3℃, 0.2C / 0.2C, 100 weeks;
[0127] Rate performance: 2C / 0.1C;
[0128] The test results are shown in Table 2.
[0129] Table 2 Performance characteristics of button batteries corresponding to Examples 1 to 3 and Comparative Examples 1 to 6
[0130]
[0131] It can be seen from Table 2 that the discharge capacity and first efficiency of the button cells using the graphite composite materials of Examples 1 to 3 are significantly higher than those of Comparative Examples 1 to 6. The experimental results show that the reason is that the graphite composite material coated with lithium reduces the irreversible capacity of the material and improves the first efficiency, while the doping of heteroatoms improves the electronic conductivity of the material and improves the rate performance.
[0132] The graphite composite materials of Examples 1 to 3 and Comparative Examples 1 to 6 are used as negative electrode active materials and the positive electrode active materials are ternary materials (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2), electrolyte and diaphragm are assembled into a 5Ah soft pack battery. The diaphragm is celegard 2400, and the electrolyte is LiPF6 solution (the solvent is a mixed solution of EC and DEC with a volume ratio of 1:1, and the concentration of LiPF6 is 1.1 mol / L). The prepared soft pack battery is tested for its cycle performance and rate performance. The test results are detailed in Table 3.
[0133] Cycle performance: The battery's 500-cycle cycle performance is tested at a charge and discharge rate of 1C / 1C, a voltage range of 2.8V-4.2V, and a temperature of 25±3℃;
[0134] Rate performance: Charge the battery to 100% SOC at a rate of 2C using constant current + constant voltage mode, and then calculate the constant current ratio = constant current capacity / (constant current capacity + constant voltage capacity).
[0135] Table 3 Performance characteristics of soft-pack batteries corresponding to Examples 1 to 3 and Comparative Examples 1 to 6
[0136] Capacity retention rate after 500 cycles (%) Rate performance (%) Example 1 94.65 94.5 Example 2 94.38 93.7 Example 3 95.11 94.9 Comparative Example 1 89.34 90.6 Comparative Example 2 88.13 88.9 Comparative Example 3 86.65 86.5 Comparative Example 4 87.11 87.3 Comparative Example 5 85.23 84.9 Comparative Example 6 84.98 82.3
[0137] It can be seen from Table 3 that the cycle performance of the battery of the embodiment is significantly better than that of the comparative example. The reason is that the lithium salt in the graphite composite material obtained in the embodiment reduces the consumption of lithium ions during the charge and discharge process and has a high liquid retention performance, thereby improving its cycle performance; at the same time, the embodiment material has a high diffusion coefficient and a low resistivity, thereby improving the fast charging performance.
[0138] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A method for preparing a graphite composite material, characterized in that: The following steps are involved: S10, obtaining amidated graphite, mixing the amidated graphite, lithium peroxide, a hydrogen peroxide solution, and an organic acid reagent, and performing a cross-linking reaction to obtain an intermediate; S20, mixing the intermediate with a curing agent containing an aldehyde group and asphalt, and sequentially performing a curing reaction and a carbonization reaction to obtain the graphite composite material.
2. The method for preparing the graphite composite material according to claim 1, characterized in that: In step S10, the step of obtaining amidated graphite includes: S01, obtaining carboxylated graphite, mixing the carboxylated graphite, an organic solvent, and an acyl chloride reagent, and performing an acyl chloride reaction to obtain acyl chloride graphite; S02, mixing the acyl chloride graphite with a solution of an amino compound, and performing an amide reaction to obtain amidated graphite.
3. The method for preparing the graphite composite material according to claim 2, characterized in that: In step S01, the step of obtaining carboxylated graphite includes: Graphite is mixed with a mixed acid solution and subjected to an oxidation reaction to obtain carboxylated graphite.
4. The method for preparing the graphite composite material according to claim 3, characterized in that: The mass ratio of graphite to mixed acid is 100:(500-1000); and / or, The mixed acid comprises sulfuric acid and nitric acid, wherein the volume ratio of sulfuric acid to nitric acid is (1-3):1, the mass percentage concentration of sulfuric acid is 70wt%-98wt%, and the mass percentage concentration of nitric acid is 50wt%-70wt%; and / or, The oxidation reaction time is 12 to 72 hours.
5. The method for preparing the graphite composite material according to claim 2, characterized in that: In step S01, the mass ratio of the carboxylated graphite, the organic solvent and the acyl chloride reagent is 100:(500-1000):(10-50); and / or, In step S01, the organic solvent includes N-N-dimethylformamide; and / or, In step S01, the acyl chloride reagent includes thionyl chloride; and / or, In step S01, the temperature of the acyl chlorination reaction is 50-100° C.; and / or, In step S01, the acyl chlorination reaction time is 12 to 24 hours; and / or, In step S02, the mass ratio of the graphite chloride to the solution of the amino compound is 100:(10-30); and / or, In step S02, the mass percentage concentration of the amino compound in the amino compound solution is 3wt% to 30wt%; and / or, In step S02, the amino compound in the amino compound solution includes at least one of aniline, dimethylamine and trimethylamine; and / or, In step S02, the amide reaction time is 1 to 6 hours; and / or, The temperature of the amide reaction is 0-10°C.
6. The method for preparing the graphite composite material according to claim 1, characterized in that: In step S10: The mass ratio of the amidated graphite, the lithium peroxide, the hydrogen peroxide solution and the organic acid reagent is 100:(10-30):(10-30):(5-15), and the mass percentage concentration of hydrogen peroxide in the hydrogen peroxide solution is 10wt%-30wt%; and / or, The organic acid reagent comprises one of acetic acid, malic acid, oxalic acid or citric acid; and / or, The temperature of the cross-linking reaction is 50-100° C.; and / or, The cross-linking reaction time is 1 to 6 hours.
7. The method for preparing the graphite composite material according to claim 1, characterized in that: In step S20: The mass ratio of the intermediate, the aldehyde-containing curing agent and the asphalt is 100:(5-15):(5-15); and / or, The aldehyde-containing curing agent comprises at least one of p-hydroxybenzaldehyde, vanillin and syringaldehyde; and / or, The curing reaction temperature is 400-600° C.; and / or, The curing reaction time is 1 to 6 hours; and / or, The temperature of the carbonization reaction is 1000-1400° C.; and / or, The carbonization reaction time is 1 to 6 hours.
8. A graphite composite material, characterized in that: The graphite composite material is prepared by the preparation method of any one of claims 1 to 7.
9. The graphite composite material according to claim 8, characterized in that The particle size of the graphite composite material is 10 to 15 μm.
10. A lithium ion battery, characterized in that: The invention comprises a graphite composite material prepared by the method for preparing a graphite composite material according to any one of claims 1 to 7 or a graphite composite material according to any one of claims 8 to 9.
Citation Information
Patent Citations
Lithium ion battery anode material suitable for low temperature and preparation method thereof
CN108598437A
Method for preparing graphene based on embedding of Li2O2 into graphite layer
CN111943174A
Graphene modified epoxy resin floor paint and preparation method thereof
CN114350229A
Long-circulation negative electrode material as well as preparation method and application thereof
CN117476859A
Cited By
Preparation method of graphite composite material
CN121672515A